Investigating Insects with Light Diode Lights for Fish Food (The Peerian Journal, 2022)
In the article, in order to obtain fish productivity of ponds, it is necessary to increase the proportion of the feed base of ponds and reservoirs in the fish feeding diet using natural feed resources. The description of two LED electrical installations for attracting various insects to fish ponds is given. The first one is tuned to a certain optimal color of the radiation. The chromaticity coordinates of the RGB-LED light emitting diodes of the second electro-optical converter vary depending on the ambient temperature.